Tumor Resection, Reconstruction, and Ankle Fusion for Recurrent Giant Cell Tumor of the Distal Tibia - Alok C. Agrawal; Mukund Madhav Ojha; Somok Banerjee (Journal of Orthopedics, Traumatology and Rehabilitation)
Giant cell tumor (GCT) is a common, mostly benign, locally aggressive tumor of bone. Distal femur, proximal tibia, and distal radius appear to be the most affected parts of the skeleton. We are reporting a case of recurrent GCT involving the distal tibia treated with resection and arthrodesis of the ankle using contralateral fibular strut graft. A male patient presented to us with pathological fracture of the left distal tibia due to recurrent GCT. Radiological assessment was suggestive of locally aggressive tumor involving the meta-epiphyseal region. The patient underwent wide margin excision of tumor and ankle fusion using the contralateral fibula as a second pillar to increase the stability of construct. GCT involving the distal tibia is a rare presentation and demands meticulous efforts to manage after recurrence. Resection of tumor mass and ankle arthrodesis is a good option as it provides a stable ankle and overall good patient satisfaction.